On the seasonal variability of eddy kinetic energy in the Gulf Stream region - Zhai, X; Greatbatch, R; Kohlmann, J (2008)
In the Gulf Stream region, eddy kinetic energy (EKE) peaks in summer while, as measured by the baroclinic eddy growth time scale, the ocean is most baroclinically unstable in late winter. We argue that the seasonally-varying Ekman pumping is unlikely to be responsible for the seasonal variation in growth time, and that the summer peak in EKE results from a reduction in dissipation in summer compared to winter. Copyright 2008 by the American Geophysical Union.